2020
DOI: 10.1002/lary.28535
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tinnitus and Associated Factors Among Asian Americans: Results From a National Sample

Abstract: Objectives: A previous study demonstrated low rates of high-frequency hearing loss and noise exposure among Asian Americans (AAs). This study examined the prevalence of tinnitus and associated factors among AAs using the first nationally representative sample of AAs. Study Design: Cross-sectional analysis of a national health survey. Methods: We analyzed data from the 2011 to 2012 National Health and Nutritional Examination Survey, during which 3,669 participants aged 20 to 69 years completed questionnaires on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…We found that the likelihood of tinnitus was lower for male workers born in Asia. This finding is consistent with a report that the prevalence of tinnitus among American Asians is significantly lower than for other American ethnic groups, although the difference was reduced by adjusting for comorbid conditions, noise exposure, and depression 21 …”
Section: Discussionsupporting
confidence: 92%
“…We found that the likelihood of tinnitus was lower for male workers born in Asia. This finding is consistent with a report that the prevalence of tinnitus among American Asians is significantly lower than for other American ethnic groups, although the difference was reduced by adjusting for comorbid conditions, noise exposure, and depression 21 …”
Section: Discussionsupporting
confidence: 92%
“…Lastly, this study's results may not be entirely comparable for other racial/ethnic groups as the original population was drawn from a predominately Taiwanese Asian demographic. A large-scale cross-sectional study from the United States has shown that tinnitus prevalence is significantly lower among Asians than other ethnic groups 42 . Ethnicity status has been suggested to be another independent factor that influences the risk of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…37 Another study from populations of Asian Americans showed hypertension or diabetes mellitus were not associated with tinnitus prevalence. 38 The sample size in the 3 studies of patients with systemic diseases 21,33,35 ranged from 115 to 255, and the prevalence ranged from 38.6 per cent to 51.6 per cent.…”
Section: Discussionmentioning
confidence: 99%